Avaliaç\~ao do gasto tributário em saúde: O caso das despesas médicas do Imposto de Renda da Pessoa Física (IRPF) - Carlos Octávio Ocké-Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– Considering the de-financing of the Brazilian Unified Health System (SUS), the health-related tax expenditure seems to be undesirable under the distributive justice approach. It represents an unpaid tax or public expenditure not directly applied to health policies, promoting, among others, the profit of the private sector. In the context of fiscal constraints, looking over its magnitude and inequity that favors the upper income - the government should reflect how this problem can be tackled. This rebate represents a significant amount of funds not collected by the Individual Income Tax (IRPF), which is in part transferred to states and local authorities, playing a significant role in the SUS financing at poorest regions. This working paper evaluates the deduction of medical and hospital expenses of the IRPF, taking the opportunity to debate some ideas to eliminate, reduce or target such subsidies. It appears that any changes in the design and magnitude of the tax expenditure can be applied to different purposes. However, besides its increasing growth, the subsidy size is so significant that once allocated for other priorities, it might serve as a basis for creating social programs or for boosting existing programs, or even compensate effects on the tax burden, addressing the poverty and structural inequality in the society. If managed properly, this mechanism could contribute to overcoming certain inequities in the Brazilian health system.
Keywords: H51; 330; government expenditures and health; equity; health care financing; allocation of health resources; health-related tax expenditure